A PANEL DATA ANALYSIS OF THE RELATIONSHIP BETWEEN LEAGUE PERFORMANCE AND THE SHARES OF THE PUBLICLY-TRADED FOOTBALL CLUBS - Findikçi, Mefule; Tapşin, Gülçin (European Scientific Journal, ESJ, 2015)
Financial analysis of football clubs have gained great importance with the increase in the added value created by these institutions which have had a large share in the sports industry in recent years. The aim of this study is to investigate the relationship between the financial performance of the joint-stock companies belonging to the sport clubs which are traded in Istanbul Stock Exchange (BIST) and the sporting achievements of the professional football branches of sports clubs in Spor Toto Super League. Within this scope, it is aimed to determine in what aspects the share earnings that belong to Beşiktaş, Galatasaray, Fenerbahçe and Trabzonspor Clubs are affected by the match results (win, defeat or draw), and by the difference between the numbers of scored and conceded goals in five seasons between the years 2010 and 2015 by using panel data analysis. Moreover, to analyze the effect of the current market, the variables BIST Sporting Index and BIST 100 Index return values were included in the model.